1994
DOI: 10.1007/bf00968996
|View full text |Cite
|
Sign up to set email alerts
|

Neuroblast cell death in ovo and in culture: Interaction of ethanol and neurotrophic factors

Abstract: We used two experimental paradigms to examine the influence of the neurotrophins, NGF, EGF, and bFGF on normal neuroblast survival and also after ethanol insult. In the first paradigm, chick embryos received in ovo at embryonic day 1 and 2 (E1 and E2) saline (control) ethanol (10mg/50 microliters/day), NGF (50 ng/50 microliters/day), or EGF (25 ng/50 microliters/day), or ethanol+NGF or EGF. At E3, cultures were prepared from whole embryos separately from each group. At C2, all cultures were labeled with [3H]th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1995
1995
1997
1997

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…The identification of protective factors is an important prerequisite for effective therapeutic strategies directed towards the treatment of FAS. Previous research suggested that members of the neurotrophin and fibroblast growth factor families of growth factors (NGF and bFGF, respectively) can ameliorate ethanol-induced cell loss in whole-embryo dissociated cultures as well as in PC12 cells Pantazis et al, 1992;Rahman et al, 1994). However, there may be a regional specificity in the sensitivity of neurons to different growth factors.…”
Section: Gdnf Attenuation Of Ethanol Neurotoxicitymentioning
confidence: 95%
“…The identification of protective factors is an important prerequisite for effective therapeutic strategies directed towards the treatment of FAS. Previous research suggested that members of the neurotrophin and fibroblast growth factor families of growth factors (NGF and bFGF, respectively) can ameliorate ethanol-induced cell loss in whole-embryo dissociated cultures as well as in PC12 cells Pantazis et al, 1992;Rahman et al, 1994). However, there may be a regional specificity in the sensitivity of neurons to different growth factors.…”
Section: Gdnf Attenuation Of Ethanol Neurotoxicitymentioning
confidence: 95%
“…This has also been identified as the time frame during which ethanol has the greatest effect to limit neuronal survival in culture (Rahman et al, 1994b). Thus, for the purposes of this study, we were interested in that population of neuroblasts "born" between 0-3 DIV (i.e., those which incorporated BrdU into nuclear DNA).…”
Section: Differential Development Of Neuronal Phenotypes In Culturementioning
confidence: 99%
“…Such parameters as neuronal migration (Miller, 1993), and . phenotypic expression Vernadakis, 1990a, 1992;Rahman et al, 1994a) and survival (Kentroti and Vernadakis , 199 1 a;Rahman et al, 1994b), are affected by prenatal ethanol exposure. Previous reports from our laboratory have demonstrated that exposure of chick embryos to ethanol at an early stage of embryogenesis (days 1-3 of development), when neuroblasts remain pluripotential, results in decreased cholinergic and increased catecholaminergic and GABAergic expression in whole brain and cerebral hemispheres when examined at embryonic day 8 (Kentroti and Vernadakis, 1990a, 1991a, 1992.…”
Section: Introductionmentioning
confidence: 99%
“…This study focuses on the marked differences between those glia (E3) and glial populations from more advanced stages of development (E15) with respect to differentiation and phenotypic expression. In a series of related studies, we have shown that prenatal ethanol exposure markedly alters both morphological and biochemical properties of developing neurons both in ovo and in culture (Kentroti and Vernadakis, 1990;Rahman et al, 1993Rahman et al, , 1994a and, more importantly, that the effects are restricted to a critical period of sensitivity occurring very early during development (Kentroti and Vernadakis, 1990). These data attest to the profound differences in the same cell populations (both neurons and glia) when examined at different stages of development.…”
Section: Introductionmentioning
confidence: 78%
“…A recent study by Valles et al (1994) suggests a decrease in secretion of NGF by proliferating astrocytes in cultures derived from rats prenatally exposed to ethanol. In addition, we have found that NGF, when given concomitantly with ethanol (and during the critical window of development), can ameliorate the neuronotoxicity of ethanol (Rahman et al, 1993(Rahman et al, , 1994a. While the content of NGF in ovo increased markedly in whole brain between 3 and 15 days of development, in cerebral hemispheres (the source for E15 glia and the site of cholinotoxicity of ethanol), NGF content did not differ significantly between E3 and E14.…”
Section: Introductionmentioning
confidence: 92%